Dependence of short-channel effects on semiconductor bandgap in tunnel field-effect transistors - Nguyễn, Đăng Chiến (2023)
Scaling down the bandgap is considered as an essential approach to enhance the performance of tunnel field-effect transistors (TFETs). Using two-dimensional simulations, this study examines the dependence of short-channel effects on the semiconductor bandgap in TFETs. It is shown that the short-channel effect is more severe with using lower bandgap materials although the supply voltage is scaled in parallel with the bandgap. For a given bandgap material, the short-channel effect can be well evaluated by the increase of drain-induced barrier thinning (DIBT) with decreasing the channel length. For different bandgap TFETs, however, their short-channel effects cannot be compared properly by comparing the DIBTs. Adequately considering the effect of bandgap on the TFET scalability is necessary in designing scaled integrated circuits.